Freedom as self-realization : Zide in the Neo-Daoist Philosophy of Guo Xiang - Tan, Christine Abigail Lee (Nanyang Technological University, 2021)
Freedom is a value cherished by most, and yet it is defined in as many ways as there are people defining it. Possibly one of the most elusive concepts in the history of philosophy, it has definitely been a controversial one in relation to Chinese philosophy—that is, whether or not it even exists, and if so, what it means in such a context. This work examines the potential of Guo Xiang’s philosophical enterprise to contribute insights to these pressing concerns. Moreover, it aims to provide a comprehensive account of a kind of freedom that is both ontological and political. As such, the study will focus on Guo Xiang’s notion of self-realization (自得 zide), and argue that this conception of freedom introduces a “dependence-based autonomy.” Emerging at a chaotic but also syncretic time in the development of Chinese Philosophy, this notion of freedom is largely ontological and epistemological in nature, yet show considerable potential in understanding social and political freedom. I suggest thus that Guo Xiang’s philosophy allows us to conceive of a type of freedom which is necessary in as much as it is contingent. This articulation of freedom as self-realization (zide), is thus both ontological and political on account of a “logic of convergence.” Such logic has the radical potential to shed light upon the problem of freedom, because it goes beyond dissolving, allowing an absolute convergence of binaries, not only between particular and universal, but also ultimately between self and other.